PERAN GURU DALAM MENGOPTIMALKAN MULTIPLE INTELEGENCY SISWA MTSN PACITAN - Khusnul Hamdani, Mohammad (LPPM STAI Muhammadiyah Probolinggo, 2023)
The potential of students who are different from one another provides color in the school environment. Every student at least has a tendency to have skills or potential. The potential of students needs a companion in discovering the potential of each student. MTsN Pacitan provides facilities to help develop students according to their skills. The teacher provides direction by knowing the abilities of each student. Some incidents that are of concern and student abilities at least need to be observed and adjusted accordingly. Teacher attention is needed to help students discover their potential. This research uses a type of qualitative research based on reality in the field. Apart from that, this research uses interviews, observation and documentation in collecting data. That in research there are results which state that students have a bias in their potential depending on influence from friends or from themselves. Apart from that, there are significant differences between students depending on the abilities of each student. Apart from that, students have different abilities according to their talents and interests. Students have different intelligences that suit their respective abilities.